2020
DOI: 10.1007/s40268-020-00315-2
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Magnesium Sulfate in Preeclampsia and Associated Factors

Abstract: Background and Objective The pharmacokinetic basis of magnesium sulphate (MgSO 4) dosing regimens for preeclampsia (PE) prophylaxis and treatment is not clearly established. The aim of study is to develop a population pharmacokinetic (PK) model of MgSO 4 in PE, and to determine key covariates having an effect in MgSO 4 pharmacokinetics in preeclampsia (PE) and to determine key covariates having an effect in MgSO 4 PK. Methods A prospective cohort study was conducted from June 2016 to February 2018 in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…The latest guidelines are for the administration of magnesium sulfate in patients with serious preeclampsia for seizure prophylaxis. Although magnesium sulfate is not threat-free, the key benefit of magnesium is its long safety record for mothers and children while avoiding maternal seizures [12] [13].…”
Section: Advances In Health Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest guidelines are for the administration of magnesium sulfate in patients with serious preeclampsia for seizure prophylaxis. Although magnesium sulfate is not threat-free, the key benefit of magnesium is its long safety record for mothers and children while avoiding maternal seizures [12] [13].…”
Section: Advances In Health Sciencesmentioning
confidence: 99%
“…The maximum score obtainable was (15) while the minimum score was (0). Scores from (0-5) show "poor knowledge," scores from (6-10) show "good knowledge" and scores from (11)(12)(13)(14)(15) show "excellent knowledge".…”
Section: Scoring System Of the Study Toolmentioning
confidence: 99%
“…There are, however, no available pharmacokinetic studies available that report a minimum effective analgesic concentration for magnesium. Magnesium sulphate pharmacokinetic models are only available for pregnant women, specifically aimed at those with pre‐eclampsia [29, 30]. Both analyses found that renal dysfunction (based on serum creatinine levels) affected magnesium sulphate pharmacokinetics and it should, therefore, be used with caution in patients with abnormal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The current knowledge on the role of magnesium treatment in PE with severe features has focused on the study of magnesium sulfate (MgSO 4 ; Amaral et al, 2017;Chiarello et al, 2018). MgSO 4 is an important pharmacological tool used to treat PE with severe features because it can prevent the recurrent seizures of eclampsia and tocolysis in preterm labor (Sibai, 2005;Smith et al, 2013;Da Costa et al, 2020). This salt is mainly administered intravenously because the oral route is well known to produce gastrointestinal effects and it is poorly absorbed in the gut (Lu and Nightingale, 2000).…”
Section: Introductionmentioning
confidence: 99%